Expansão da educação superior, cursos de licenciatura e criação das novas universidades federais - Camargo, Arlete Maria Monte de; Medeiros, Luciene das Graças de Miranda (Revista Educação em Questão, 2018)
This article aims to analyze the repercussions of higher education policies in federal public universities (created between 2003 and 2014), affected by economic and financial constraints, especially considering undergraduate courses. It is considered that social policies assume the determination to legitimize the social relations of production, as well as the commitment to attend to the demands of the working class, for access to higher education. (CHESNAIS, 1995; PAULANI, 2008; NEVES, 2007). the review of the related literature was done, and the INEP / MEC database and the sites of the federal universities researched were used, where a clearer view was given on the offer of courses in each of these IES Among the results, the construction of new academic architectures in undergraduate courses and a new academic-institutional culture, although there is still room for the task of training teachers in the university space, which is not a priority in some institutions studied.